Tingkat keberlanjutan terhadap aspek pengelolaan sumur tua secara tradisional di Bojonegoro Jawa Timur - Ahmad Kurnain; Yusni Ikhwan Siregar; Sri Indarti; Suwondo Suwondo (Pelantar Press, 2021)
This study aims to determine the sustainability status of the Re-Opening Oil Wells of Bojonegoro Regency, East Java, Indonesia. The method used in this research is Multidimensional Scaling analysis which is implemented using Rap-Re-Opening Oil Wells software. Existing status of Wells Bojonegoro Re-Opening Oil Sustainability Less Sustainable with the weighting value of each dimension is 34.56%, 39.73%, 45.25%, 37.90%, 57.00%. The strategy to increase the addition of status values from the 5 dimensions of the Sustainability Index, evaluated only one dimension that is sustainable with a fairly good status. The results obtained from the improvement scenario obtained by the respective percentage figures as follows; Ecology 41.44%, Economics 61.62%, Social and Culture 45.25%, Technology 42.02%, Institutional 61, 29%. Thus the strategy to increase sustainable status can be improved by the Oil Wells Rap-Re-Opening Method.